Early Life Exposure to the Great Chinese Famine (1959–1961) and the Health of Older Adults in China: A Meta-Analysis (2008–2023) - Chi Shen; Xi Chen (Institute of Labor Economics (IZA), 2024)
There is mounting evidence indicating that the aging process initiates during early life stages, with in utero the individual's environment playing a significant role. Consequently, it is crucial to understand the enduring effects of early life circumstances on health in old age. In this study, we conducted a meta-analysis to examine the effects of the Great Chinese Famine (1959–1961) on the health of older adults. We also explored potential mechanisms underlying these effects. The complex interplay between early life circumstances, multiple health-related sectors, and healthy aging necessitates a comprehensive life-course approach and strategic interventions to enhance public health in an aging society.
Keywords: I14; J14; J13; I18; 330; early life circumstances; famine; life course health; aging; meta-analysis